It looks like you're using an Ad Blocker.
Please white-list or disable AboveTopSecret.com in your ad-blocking tool.
Thank you.
Some features of ATS will be disabled while you continue to use an ad-blocker.
abecedarian
y = 48 / 2(9+3)
To throw fuel on the fire... lets refactor.
Start by moving the "2" (sorry for the leading zeroes- used for formatting only):
y = 48 / 2(9+3)
2 = 02 / 00002
... end up with ...
y / 2 = 24 / (9+3)
So, put that 2 back on the other side so that:
(y / 2) * 2 = (24 / (9 + 3)) * 2
y = 24 / 12 = 2 = 2 * 2 = 4
????
Maybe go the other way and move the (9+3):
y / (9+3) = (48 / (9+3)) / (2(9+3) / (9+3))
So, y / 12 = (48 /12) / (24 / 12)
Then, y / 12 = (4) / (2)
y/12 = 2; y = 24?
I need some licorice.
Waiting for someone to point out my errors.
edit on 3/2/2014 by abecedarian because: (no reason given)
dude1
if you have y/b(a+b) and y=1 b=2 its 1/2(a+b).
if you have y/b(y/b)
and y=1 b =2
y/b(y/b)=1/2(1/2) =0.25
why would addition in the parenthesis make a difference ?
NullVoid
sheepslayer247
I'm not a math wiz or anything, but I was taught the parentheses are dealt with first: (9+3) = 12
Then you would calculate 48/2: 24
So you are left with 24(12) or 24x12. That equals 288.
I'm smarter than a calculator!
I got 2.
I dont know about BODMAS or whatever, but it is a must to simplify the equation first, so...
48/2(9+3)
after (9+3) = 12, you are left with 48/ 2(12), simplify!, so 48/24, simplify! so.... 2
trying algebra approach,
a/b(x+y)
a/(bx+by)
substituting a=48,b = 2, x = 9 and y = 3...
a/b(x+y) = a/(bx+by)
a/(bx+by) = 48/2(9+3)
a/(bx+by) = 48/(2(9)+2(3))
a/(bx+by) = 48/(18+6)
a/(bx+by) = 48/(24)
a/(bx+by) = 2
notice, you still have to solve the bx+by part first ? if you solve 48/2 part first, that would break the algebra
to properly arrive at 288, a new bracket/paren should be introduce
(48/2)(9+3)
moving to algebra
(a/b)(x+y)
((a/b)x) + ((a/b)y)
substitute
((a/b)x) + ((a/b)y) = ((48/2)x) + ((48/2)y)
((a/b)x) + ((a/b)y) = (24x) + (24y)
((a/b)x) + ((a/b)y) = (24(9)) + (24(3))
((a/b)x) + ((a/b)y) = (216) + (72)
((a/b)x) + ((a/b)y) = 288
so, in short,
48/2(9+3) = 2
(48/2)(9+3) = 288
or am I missing something ?edit on 1-3-2014 by NullVoid because: (no reason given)
GogoVicMorrowThe answer is 288 when you do parenthesis first.